Membrane Vesicles Can Contribute to Cellulose Degradation by Teredinibacter turnerae, a Cultivable Intracellular Endosymbiont of Shipworms - Mark T. Gasser; Annie Liu; Marvin A. Altamia; Bryan R. Brensinger; Sarah L. Brewer; Ron Flatau; Eric R. Hancock; Sarah P. Preheim; Claire Marie Filone; Daniel L. Distel (Microbial Biotechnology)
ABSTRACT Teredinibacter turnerae is a cultivable cellulolytic Gammaproteobacterium (Cellvibrionaceae) that commonly occurs as an intracellular endosymbiont in the gills of wood‐eating bivalves of the family Teredinidae (shipworms). The genome of T. turnerae encodes a broad range of enzymes that deconstruct cellulose, hemicellulose and pectin and contribute to wood (lignocellulose) digestion in the shipworm gut. However, the mechanisms by which T. turnerae secretes lignocellulolytic enzymes are incompletely understood. Here, we show that T. turnerae cultures grown on carboxymethyl cellulose (CMC) produce membrane vesicles (MVs) that include a variety of proteins identified by liquid chromatography–mass spectrometry (LC–MS/MS) as carbohydrate‐active enzymes (CAZymes) with predicted activities against cellulose, hemicellulose and pectin. Reducing sugar assays and zymography confirm that these MVs exhibit cellulolytic activity, as evidenced by the hydrolysis of CMC. Additionally, these MVs were enriched with TonB‐dependent receptors, which are essential to carbohydrate and iron acquisition by free‐living bacteria. These observations indicate a potential role for MVs in lignocellulose utilisation by T. turnerae in the free‐living state, suggest possible mechanisms for host–symbiont interaction and may be informative for commercial applications such as enzyme production and lignocellulosic biomass conversion.